2013
DOI: 10.1016/j.ifset.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of tomato peroxidase inactivation by atmospheric pressure cold plasma based on dielectric barrier discharge

Abstract: Atmospheric pressure cold plasma technology is an emerging nonthermal food technology for microbiological decontamination of food and bio-materials. This study demonstrates the applicability of in-package cold plasma technology as a novel means to inactivation of enzymes. The kinetics of inactivation of tomato peroxidase as a model enzyme was studied at 30, 40 and 50kV, for up to 5' of atmospheric air dielectric barrier discharge plasma treatments. The enzyme activity was found to decrease with both treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 244 publications
(126 citation statements)
references
References 23 publications
13
106
0
7
Order By: Relevance
“…Similar observations have been reported by Pankaj et al [55]. The raise in temperature was found to have an insignificant effect (p > 0.05).…”
Section: Quantification Of Pesticide Residues and Degradation Kineticssupporting
confidence: 91%
“…Similar observations have been reported by Pankaj et al [55]. The raise in temperature was found to have an insignificant effect (p > 0.05).…”
Section: Quantification Of Pesticide Residues and Degradation Kineticssupporting
confidence: 91%
“…We have successfully demonstrated the ability of DBD based in-package NTP in air to inactivate background microflora on strawberries, without inducing significant changes in quality [13]. Recently, our group also demonstrated the inactivation of an enzyme in tomato extract using the same plasma source [14]. We have not found significant changes in the food packaging material following NTP treatments to declare hazards from this process [15,16].…”
Section: Introductionmentioning
confidence: 86%
“…However, in the direct treatment, in addition to the mentioned RS, the short-lived RSs such as OH˙ and O 2 as well as UV may be related to the enzyme inactivation of ACP. Pankaj et al (2013) studied the effects of treatment time and voltage of the DBD plasma process on the activity of tomato peroxidase (Pankaj et al, 2013). They observed that the enzymatic activity decreased with both treatment time and voltage.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%